2021
DOI: 10.3389/fpubh.2021.768723
|View full text |Cite
|
Sign up to set email alerts
|

Stressful Life Events and Chinese Older People Depression: Moderating Role of Social Support

Abstract: Aim: This study analyzes the effects of retrospective stressful life events on current depression among Chinese older people and how these effects are moderated by social support. Stressful life events comprise bereavement, divorce, health adversities, accidents, and financial losses due to fraud.Data and Method: Data were drawn from the China Health and Retirement Longitudinal Study (CHARLS) of the 2015 panel, and responses from 9,619 older people aged over 60 years were used. The least-squares regression met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 66 publications
0
15
2
Order By: Relevance
“…Similar to previous studies, patients who have received social support experience less distress and relapse [53], can better manage psychiatric symptoms [54] and deal more effectively with stress. Therefore, our study adds context to prior literature associated with the interaction between subjective support and stressful life events, which may in uence relapse [55]. Targeted treatment of subjective social support in patients with high levels of stressful life events could play a crucial role in preventing relapse and improving outcomes in these patients.…”
Section: Discussionmentioning
confidence: 72%
“…Similar to previous studies, patients who have received social support experience less distress and relapse [53], can better manage psychiatric symptoms [54] and deal more effectively with stress. Therefore, our study adds context to prior literature associated with the interaction between subjective support and stressful life events, which may in uence relapse [55]. Targeted treatment of subjective social support in patients with high levels of stressful life events could play a crucial role in preventing relapse and improving outcomes in these patients.…”
Section: Discussionmentioning
confidence: 72%
“…For example, a study on depression in Chinese elderly (48) found that family social capital could alleviate the negative effect of NLE on depression in the elderly. The findings in this study had important applications for improving the QoL of residents.…”
Section: Discussionmentioning
confidence: 99%
“…However, social capital, as a kind of external social resource, could improve individuals' emotional experience with life events and encourage individuals to take positive coping styles to face the negative influence of life events. For example, a study on depression in Chinese elderly ( 48 ) found that family social capital could alleviate the negative effect of NLE on depression in the elderly. The findings in this study had important applications for improving the QoL of residents.…”
Section: Discussionmentioning
confidence: 99%
“…Life-course disadvantages refer to a wide spectrum of stressful socioeconomic, interpersonal, mental, and health-related conditions across the life-course, including those occurring in both childhood and adulthood [7][8][9] . Individuals with life-course disadvantages are more likely to experience depression and develop unhealthy life habits, as has been well demonstrated [10][11][12][13] . However, given the stigma of mental illness and cultural differences 14 , related evidence in the Chinese population is much less adequate than that in western populations.…”
Section: Introductionmentioning
confidence: 88%